Strong in Their Weakness or Weak in Their Strength? The Case of Lebanese Diaspora Engagement with Lebanon - Skulte-Ouaiss, Jennifer (2015)
This paper seeks to assess when and how the Lebanese Diaspora in Australia, Canada and the USA is most able to affect homeland affairs in Lebanon. Drawing on over 300 in-depth interviews and analysing literature on the Lebanese Diaspora and Lebanon itself, the article seeks to categorise the spectrum of diaspora engagement with Lebanon and more fully define the diaspora's homeland participation. Tentative conclusions indicate that the Lebanese Diaspora is most able to affect homeland affairs when the state is absent or unable to perform its functions as well as because the various political factions do not want a state built. However, to date, despite its renowned strength, the Lebanese Diaspora has not been able to affect change in the sectarian nature of Lebanese homeland politics nor in the too often replicated sectarian politics in the diaspora. We conclude that the diaspora is thus both strong and weak vis-à-vis affecting homeland public affairs.